Reinterpretasi Monumen Bagindo Aziz Chan Karya Arby Samah dalam Ikonografi Erwin Panofsky - Rian, Rica; Suryanti, Suryanti (PANGGUNG, 2020)
ABSTRACTResearch was entered to trace the Bagindo Aziz Chan monument by Arby Samah trough the iconographicapproach put forward by Erwin Panofsky, as well as to uncover the reason for the contruction of themonument. The research uses qualitative methods of observation interviews and document.The figure Arby Samah described in the “Bagindo Aziz Chan Monument” is indeed a Bagindo figure,which was made using cement plaster technique, making the work began in 1973 by Arby Samah. Reliefsmade in the foundation of the statue tells the sequence of event killed Bagindo Aziz Chan. The use ofthe realist style found by the author on the Bagindo Aziz Chan monument although the cultivation ofthe statue still looks tough, but the delivery of the sign on the statue is the hope and ideals of BagindoAziz Chan during his leadership as mayor of Padang is clearly depicted. The making of the statue uses acement plaster which is a technique commonly technique. Used by sculpture artists in the 1970s. In 2005Bagindo Aziz Chan was awarded as a national hero from west Sumatera by the central government, andalso on July 19 the people of Padang commemorated the day of death of Bagindo Aziz Chan which was atribute to the leader of Padang. And also the name Bagindo Aziz Chan has been enshrined as the name ofa street and a building in the city of Padang.Keywords: Bagindo Aziz Chan Monument, Iconographic, Erwin Panofsky.ABSTRAKPenelitian dimaksudkan untuk menelusuri monumen Bagindo Aziz Chan karya Arby Samahmelalui pendekatan ikonografi yang dikemukakan oleh Erwin Panofsky, serta mengungkapalasan dibangunnya monumen tersebut. Penelitian ini menggunakan metode kualitatif yaitupengamatan, wawancara dan dokumen.Tokoh yang digambarkan Arby Samah pada karya “Monumen Bagindo Aziz Chan” ini memangsosok Bagindo Aziz Chan, yang dibuat memakai teknik plaster semen, pembuatan karya tersebutselesai mulai dilakukan pada tahun 1971 dan selesai pada tahun 1973 yang dibuat oleh ArbySamah. Relief yang dibuat pada landasan patung menceritakan urutan peristiwa terbunuhnyaBagindo Aziz Chan. Pemakaian gaya realis yang didapati penulis pada monumen BagindoAziz Chan walaupun penggarapan patung tersebut masih terlihat kasar, namun penyampaiantanda pada patung tersebut merupakan harapan dan cita-cita Bagindo Aziz Chan selamakepemimpinannya sebagai wali kota Padang tergambarkan dengan jelas. Pembuatan patungtersebut menggunakan teknik plaster semen yang merupakan teknik yang umum dipakai olehseniman patung pada tahun 1970-an. Pada tahun 2005 Bagindo Aziz Chan dianugrahi sebagaipahlawan nasional asal Sumatera Barat oleh pemerintah pusat, dan juga pada tanggal 19 Julimasyarakat kota Padang memperingati hari wafatnya Bagindo Aziz Chan yang merupakanpenghormatan kepada pemimpin kota Padang yang tegas dan berani tersebut. Dan juga namaBagindo Aziz Chan sudah diabadikan sebagai nama jalan dan gedung di kota Padang.Kata Kunci: Monumen Bagindo Aziz Chan, Ikonografi Erwin Panofsky